Sensory Processing Difficulties in Youths With Disruptive Mood Dysregulation Disorder - Benarous, Xavier; Bury, Véronique; Lahaye, Hélène; Desrosiers, Lyne; Cohen, David; Guilé, Jean Marc (Frontiers in Psychiatry, 2020)
Difficulty modulating sensory information has been described in children with developmental disorders. However the relation of Sensory Processing Difficulties (SPD) to emotional regulation problems remains poorly understood. The aim of this study is to determine the rate and patterns of SPD in youth with Disruptive Mood Dysregulation Disorder (DMDD). Participants were DMDD patients aged 6-16 presenting at a University Hospital in outpatient or inpatient facilities (n=30). For each participant the parent-reported Sensory Profile, the Affective Lability Scale, the Beck Depression Inventory-II, the Child Behavior Checklist/4-18 and the K-SADS-PL were completed. The scores of the Sensory Profile of the DMDD youths were compared to those obtained in a clinical control group and to the manual scores for same-age typically developing youths. SPD were reported in 53% of the subjects in the DMDD group. Youths with DMDD showed a significant difference on almost all items of the Sensory Profile compared to typically developing youth. The Sensory Profile was found to discriminate best between the participants with DMDD and those in the clinical control group with regards to the category “Behavioral outcomes of sensory processing” and the factor “Fine motor/ perceptual behavior”. All types of sensory processing patterns were reported in the DMDD youths: sensation avoiding (40%), low registration (27%), sensory sensitivity (20%), and sensation seeking (10%). As a group, youths with DMDD have significantly more SPD when compared to typical youths. Therefore, SPD could be an important factor to consider in youths with DMDD when providing comprehensive assessment and therapeutic interventions.